PEMBUATAN ALAT PRAKTIKUM TERMOSKOP GUNA MENJELASKAN RADIASI KALOR BERBASIS TEKNOLOGI MURAH DAN SEDERHANA - -, Jumiati (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2016)
This research is motivated physics not only theoretical concepts but practiced, the high price and lack of funds to purchase tools practicum especially tools practicum material calor radiation, then conducted tool making practicum termoskop. The method in this research is a practical tool manufacture termoskop, test tool practicum termoskop, testÂ feasibility tool practicum termoskop. Results in making tool practicum termoskop in accordance with references, distinguish absorption in color body, bottles black absorbs calor 0,011x10-16J with the rate of absorption 1,6 x10-16W and a bottle of white 0,010x10-16J with the rate of absorption 1,4 x10-16W. LKP who presented the material in accordance with the theory of physics, obviously, simple sentences, easy to understand, could guide the students to dig up information, typeface is easy to read and attractive.